(untitled) (Altre Modernità, 2022)
Paolo Mastrocola, Luca Ricolfi, Il danno scolastico. La scuola progressiva come macchina della disuguaglianza. (Milano, La Nave di Teseo, 2021, 272 pp. ISBN 883-460-469-5) di Alfonso D’ambrosio